Zerumbone inhibits prostate cancer cell viability and induces cell death by non-apoptotic pathway (Bangladesh Journal of Pharmacology, 2016)
The aim of the present study was to investigate the role of zerumbone on the proliferation, cell cycle arrest and cell death in DU-145 prostate cancer cell lines. The MTT assay revealed that zerumbone (20 µM) reduced proliferation of DU-145 cells to 39.0% at 48 hours. It also increased the proportion of propidium iodide stained cells to 53.4% compared 1.0% in control. However, the population of annexin V-stained cells remained uneffected indicating induction of non-apoptotic cell death by zerumbone. Treatment of DU-145 cells with zerumbone (20 µM) caused 8-fold enhancement in the level of reactive oxygen species (ROS). On the other hand, exposure of the zerumbone treated DU-145 cells to glutathione inhibited the generation of ROS. Fow cytometry using propidium iodide staining revealed that zerumbone treat-ment increased proportion of cells in G1 phase to 71.3% on compared to 34.7% in the control. The results from Western blot analysis revealed a significant increase in the expression of cyclin D1 protein in DU-145 cells on treatment with 20 µM concentration of zerumbone. Thus, zerumbone treatment inhibits prostate cancer cell viability and can be used for its treatment.Video Clip of Methodology:Western blot assay: 3 min 37 sec  Full Screen   Alternative